Pengaruh Servicesacpe Terhadap Loyalitas Konsumen - Ade Nidia; Tintin Suhaeni (Jurnal Riset Bisnis dan Investasi, 2016)
Elzatta is one of the subsidiaries of PT Bezaya Group that provides fashion stuff of Muslim women and men. The company has 28 authorized outlets in Indonesia, of which 6 are located in Bandung. Servicescape which was created in the Elzatta’s store or gallery has an important part of the service to consumers that can help to build customer loyalty. With the loyalty that is built, then the consumer will make repeat purchases of the products. This study aims to determine servicescape and customer loyalty as well as the value of the influence of servicescape on customer loyalty Elzatta Bandung. The method used is quantitative research methods. Data analysis method used is the classic assumption test, simple linear regression, simple correlation, coefficient determination test, descriptive statistical tests, and hypothesis testing. Sampling that takes the consumer as much as 104 respondents. Data was collected through interviews and questionnaires with Likert scale. The research shows a result that servicescape included in the high/good criteria, with dimensions of the ambient condition, spatial/function; sign; symbol; artifacts, employee. Likewise, customer loyalty shows the results with the high/good criteria on the dimensions of repeat purchase, purchases all lines, retention, referrals. The conclusion of this study is servicescape have an influence on consumer loyalty Elzatta Bandung as 15.8%.